Fetal and maternal morbidity in pregnant patients with Lupus: a 10-year US nationwide analysis. Issue 1 (25th April 2023) - Mehta, Bella; Jannat-Khah, Deanna; Glaser, Katherine Kayla; Luo, Yiming; Sammaritano, Lisa R; Branch, D Ware; Goodman, Susan M; Lockshin, Michael; Wang, Fei; Ibrahim, Said; Salmon, Jane E
Abstract : Objective: To evaluate and quantify the indicators of fetal and maternal morbidity in deliveries for patients with systemic lupus erythematosus (SLE) compared with deliveries in patients without SLE. Methods: We used retrospective data from the National Inpatient Sample (NIS) to identify all delivery related hospital admissions of patients with and without SLE from 2008 to 2017 using ICD-9/10 codes. Fetal morbidity indicators included pre-term delivery and intrauterine growth restriction (IUGR). 21 indicators of severe maternal morbidity were identified using standard Centers for Disease Control and Prevention (CDC) definitions. Descriptive statistics, including 95% confidence intervals, were calculated using sample weights from the NIS dataset. Results: Among the 40 million delivery-related admissions, 51 161 patients were reported to have SLE. Patients with SLE had a higher risk of fetal morbidity, including IUGR (8.0% vs 2.7%) and pre-term delivery (14.5% vs 7.3%), than patients without SLE. During delivery, mothers with SLE were nearly four times as likely to require a blood transfusion or develop a cerebrovascular disorder, and 15 times as likely to develop acute renal failure than those without SLE. Conclusion: Our study demonstrates that fetal morbidity and severe maternal morbidity occur at a higher rate in patients with SLE compared with those without. This quantitative work can help inform and counsel patients with SLE during pregnancy and planning.